Leisure in Bulgaria - Keliyan, Maya B. (Sociološki pregled, 2021)
The article examines the leisure patterns in Bulgaria in comparison with other EU countries, analyzing data from Eurostat, National Statistical Institute, European Quality of Life Survey, results from the project “Local festivals: A resource of local communities for coping with crises”, etc. Bulgarians actively use the internet and social networks, but we have the difficulties to achieve a balance between work, family, and social contacts. Low incomes negatively affect leisure activities by limiting them in order to meet the basic needs of the households. Lockdown, caused by the COVID-19 pandemic, led to an increase in leisure time, but the possibilities for its use have significantly decreased. The extensive use of telework blurs the boundaries between working time and leisure.
Keywords: leisure; Bulgarian leisure patterns; community cultural centres; COVID-19 pandemic